EFFECT OF COMPLEX HOMEOPATHIC DRUG CONTAINING COENZYME Q ON PARAMETERS OF OXIDATIVE STRESS AND HEMODYNAMICS IN EXPERIMANTAL DIABETES MELLITUS - S. G. Dzugkoev; V. A. Metelskaya; I. V. Mozhaeva; F. S. Dzugkoeva (Рациональная фармакотерапия в кардиологии)
Aim. To study the influence of complex homeopathic drug ubichinon compositum on hemodynamics, Na,K-ATPase activity, parameters of oxidative stress and serum nitric oxide (NO) metabolites concentration in experimental diabetes mellitus.Materials and methods. Diabetes mellitus was induced by the administration of 5% alloxan solution to 75 rats, 15-18 mg/100 g of body weight; 20 rats without diabetes comprised control group. The parameters of macro- and microhemodynamic, lipid peroxidation, Na,K-ATPase activity, and stable NO metabolites concentration have been compared in animals with experimental diabetes mellitus under 1 month administration of ubichinon compositum (0,11 mg/100g of body weight).Results. Experimental diabetes mellitus was shown to be associated with the development of oxidative stress expressed as activation of lipid peroxidation — increase of maloniс dialdehyde (MDA) concentration both in serum and cortex and medulla substances of renal tissues. At the same time, the antioxidant potential as well as the endothelial function (assesed as NO metabolites concentration) were decreased as compared with control animals. Administration of ubichinon compositum for 1 month resulted in restoration of stable NO metabolites concentration and Na,K-ATPase activity, as well as reduction of lipid peroxidation in blood and renal tissuesConclusion. The administration of ubichinon compositum resulted in reduction of hemodynamic manifestations of microvascular complications of diabetes mellitus.